The Craft of Tally: Tracing Marketability and Economic Sustainability of Crafts - Mabrouk, Mariam (AUC Knowledge Fountain, 2025)
This thesis explores the marketability and economic sustainability of the Tally craft in Gezeirit Shandaweel, Sohag, Egypt, with a focus on how the craft navigates the tension between cultural preservation and economic adaptation. Tally, a traditional form of embroidery, has deep cultural roots in Egypt but faces significant challenges due to global market dynamics, shifting consumer preferences, and systemic institutional neglect. Through an ethnographic case study, this research investigates how artisans, institutions, and market forces interact to shape the craft's future. The study examines the role of cultural perceptions, innovation, and institutional support in fostering or hindering Tally's economic viability. By integrating theoretical frameworks from craft studies and examining key mediating factors such as gendered labour, access to markets, and the power dynamics between artisans and designers, the thesis provides a comprehensive understanding of how Tally artisans adapt to modern demands while maintaining cultural integrity. The research also identifies gaps in institutional support and offers policy recommendations for improving the craft’s sustainability. Ultimately, this thesis contributes to the growing discourse on the sustainability of traditional crafts in the Global South, emphasising the need for systemic change to support the livelihoods of artisans and preserve cultural heritage.